Analysis of Parenting Patterns and Environmental Factors on Children's Cognitive Development: Analysis of Parenting Patterns and Environmental Factors on Children's Cognitive Development - Bariroh, Zahroul (Maliki Interdisciplinary Journal, 2025)
This study analyzes parenting patterns and environmental factors on children's cognitive development in Kluwut Village. The method used in this community service is Participatory Action Research (PAR), which aims to produce concrete actions based on the results of previous research. This approach allows participants, including teachers and parents of Dharma Wanita Persatuan 02 Kluwut Kindergarten, to actively solve parenting problems to improve children's cognitive development. The results of the community service indicate that the active involvement of parents and the social environment has a significant impact on children's cognitive development. With full support from community service partners, this program is expected to increase awareness and effectiveness of parenting strategies implemented by parents and teachers in shaping optimal children's cognitive development.